Comparison outcome in management of femoral neck fracture using multiple cancellous screws with and without fibular graft - Teguh Wisesa, I. Komang Indra; Suryanto Dusak, I. Wayan (International Journal of Research in Medical Sciences, 2020)
Multiple cancellous cannulated screw is preferred method in fresh cases of fracture neck of femur in young patients. Fibular strut graft is sometimes used along with multiple cancellous cannulated screws to enhance union and early restoration of function. We conducted a retrospective study to patients aged between 20-50 years old with femoral neck fracture treated with multiple cancellous screws either with or without fibular graft between the period of January 2016 to January 2018. We obtained total of six patients (five males and one female) with femoral neck fracture treated with multiple cancellous screws either with or without fibular graft. All fractures were garden type II-IV fresh femoral neck fractures. The functional outcome based on Harris hip score was excellent for all patients. The mean time of full weight bearing was 16±8 weeks in both multiple cancellous screws without fibular group and multiple cancellous screws with fibular group. The mean time of union was also 16±8 weeks in both groups. There is no complication such as non-union, avascular necrosis of femoral head and/or broken fibular graft in both the groups occurrences. Fixation with cancellous screws and fibular strut grafts for femoral neck fractures is cost effective and technically less demanding and associated with good outcomes. There is no added advantage of non-vascularized fibular grafting with multiple hip screw fixation in fresh femoral neck fractures in young adults over multiple hip screw fixation alone.